2004
DOI: 10.1038/sj.bmt.1704781
|View full text |Cite
|
Sign up to set email alerts
|

Can the stem cell mobilization technique influence CD34+ cell collection efficiency of leukapheresis procedures in patients with hematologic malignancies?

Abstract: Summary:A total of 415 leukaphereses in 201 patients stimulated with growth factor (GF; n ¼ 119) or chemotherapy-GF (n ¼ 296) were studied to determine CD34 þ cell collection efficiency (CE). The pre-apheresis leukocyte count was 1-93 Â 10 9 /l (median 20), and peripheral blood CD34 count (PBCD34) was 1-1104/ll (median 19). The total number of CD34 þ cells collected was 4-6531 Â 10 6 (median 151); corresponding to 0.1-111.4 Â 10 6 (median 2.3) per kg. There was strong correlation between PBCD34 and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
6
22
0
Order By: Relevance
“…As reported previously 6 days of rcG‐CSF treatment increased total white blood cell, neutrophil, and monocyte counts in healthy and LPD dogs with no apparent clinical side effects. The rhG‐CSF treatment enabled us to harvest >2 × 10 6 CD34+ cells/kg with 1 apheresis in 10/11 mobilized LPD dogs, which is the target dose in humans needed to ensure appropriate hematologic reconstitution in most transplant patients . In addition, all dogs also received a double dose of rhG‐CSF approximately 2 hours before apheresis to maximize CD34+ cell yield…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As reported previously 6 days of rcG‐CSF treatment increased total white blood cell, neutrophil, and monocyte counts in healthy and LPD dogs with no apparent clinical side effects. The rhG‐CSF treatment enabled us to harvest >2 × 10 6 CD34+ cells/kg with 1 apheresis in 10/11 mobilized LPD dogs, which is the target dose in humans needed to ensure appropriate hematologic reconstitution in most transplant patients . In addition, all dogs also received a double dose of rhG‐CSF approximately 2 hours before apheresis to maximize CD34+ cell yield…”
Section: Discussionmentioning
confidence: 93%
“…This ratio was reduced to 8 : 1 after the 5th LPD dog apheresis, due to product clumping after overnight refrigeration. For all aphereses, the procedure length was based on body weight . Aphereses run lengths were based on a canine total blood volume (TBV) of 90 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility is that we opted for two more harvests than the default in Spectra‐Auto collection, which may contribute to an overall higher yield due to fewer overflown cells in the harvests. In addition, increased preapheresis peripheral WBC counts in Spectra‐MNC may have contributed, because it has been reported that the increased peripheral WBC count is associated with decreased CE of CD34+ cells 9,24‐27. In fact, with Spectra‐MNC, preapheresis WBC counts were positively correlated with the collection yields of WBCs and inversely correlated with the CE of CD34+ cells.…”
Section: Discussionmentioning
confidence: 98%
“…Difficulty mobilizing CD34+ cells has also been described as a poor prognostic factor in terms of predicting engraftment delay and worse event-free survival despite transplanting adequate CD34+ cell doses (27, 28). High peripheral blood WBC and granulocyte counts as seen with mobilization using only hematopoietic growth-factor (GF) stimulation are associated with decreased CD34+ cell collection efficiency and a higher rate of granulocyte contamination of the PBSC product(29, 30). Cooling et al recently reported that chemotherapy and GF mobilization along with manual collection on the COBE Spectra instrument with the WBC kit improved CD34+ cell yield and decreased the granulocyte content and infusion reaction rates as compared to mobilization with GF only and use of AUTO-kits (24).…”
Section: Discussionmentioning
confidence: 99%